Prevalence of Campylobacter spp. on retail fresh chicken carcasses in Hanoi, Vietnam - Vu Dung Minh; Meeyam, T.; Unger, Fred; Gölz, G.; Pham Thi Ngoc; Truong Thi Huong Giang; Alter, T.; Pichpol, D. (Chiang Mai University, 2023)
This study was conducted to determine the prevalence of Campylobacter spp. on fresh chicken carcasses at retail markets in four selected urban districts in Hanoi, Vietnam. A total of 107 chicken carcass samples were collected. Campylobacter spp. was found on 44 chicken carcasses and accounted for a prevalence of 41.1%. Among the Campylobacter species detected, C. coli was the predominant Campylobacter spp., being detected in 24 of the 44 samples, followed by C. jejuni, detected in 19 of 44 samples. One carcass was positive for both C. jejuni and C. coli. The high prevalence of zoonotic C. jejuni and C. coli on chicken carcasses emphasizes the need to enhance awareness of the public and relevant stakeholders on food safety and foodborne diseases in Vietnam.